Influencia de la fertilización potásica en el rendimiento y calidad del pepino (Cucumis sativus L.) una revisión al estado del arte - Haz Villamar, Henrry Franchesco (2021)
The main objective of the research was to review the state of the art related to the influence of potassium fertilization on the productivity and quality of cucumber. The study was developed in the library at ESPAM MFL polytechnic campus located at El Limón site, belonging to Bolívar canton, Manabí. The methodology implemented was qualitative and interpretative. A bibliographic matrix designed in Excel was used where all the texts that made up the universe were inventoried and on which selection filters were applied to locate, identify and access those documents that contained the pertinent information for the investigation. A total of 80 documents of various types of material were reviewed. Concluding that potassium has essential functions in protein synthesis, enzymatic activities, photosynthesis, energy transfer, transport in the phloem, in the osmoregulation that takes place in the processes of opening and closing stomata anion-cation balance and resistance to biotic stress and abiotic. In the same way, it influences the productivity and quality of the cucumber, increases the number of fruits, fruit weight, diameter and length of fruits, concentrating its greater nutritional demand, in the phenological stages of fruiting and harvesting. Chronologically, potassium fertilization is reported at the beginning of the 19th century and in the 60s with the "green revolution", where potassium was identified as one of the three critical factors responsible for the productivity and quality of cucumber.